Hematopoietic Stem Cell Transplantation in Primary Immunodeficiency Diseases: Current Status and Future Perspectives - Castagnoli, Riccardo; Delmonte, Ottavia Maria; Calzoni, Enrica; Notarangelo, Luigi Daniele (Frontiers in Pediatrics, 2019)
Primary immunodeficiencies (PID) are disorders that for the most part result from mutations in genes involved in immune host defense and immunoregulation. These conditions are characterized by various combinations of recurrent infections, autoimmunity, lymphoproliferation, inflammatory manifestations, atopy, and malignancy. Most PID are due to genetic defects that are intrinsic to hematopoietic cells. Therefore, replacement of mutant cells by healthy donor hematopoietic stem cells (HSCs) represents a rational therapeutic approach. Partial or full ablation of the recipient’s marrow with chemotherapy is often used to allow stable engraftment of donor-derived HSCs, and serotherapy may be added to the conditioning regimen to reduce the risks of graft rejection and graft-versus-host disease. Initially, hematopoietic stem cell transplantation (HSCT) was attempted in patients with severe combined immunodeficiency (SCID) as the only available curative treatment. It was a challenging procedure, associated with elevated rates of morbidity and mortality. Overtime, outcome of HSCT for PID has significantly improved due to availability of high-resolution HLA typing, new stem cell sources, increased use of alternative donors, development of less toxic, reduced-intensity conditioning regimens, and cellular engineering techniques for graft manipulation. Early identification of infants affected by SCID, prior to infectious complication, through newborn screening (NBS) programs and prompt genetic diagnosis with Next Generation Sequencing (NGS) techniques, have also ameliorated the outcome of HSCT. In addition, HSCT has been applied to treat a broader range of PIDs, including disorders of immune dysregulation. Yet, the broad spectrum of clinical and immunological phenotypes associated with PIDs makes it difficult to define a universal transplant regimen. As such, integration of knowledge between immunologists and transplanters is necessary for the development of innovative transplant protocols and to monitor their results during follow-up. Despite the improved outcome observed after HSCT, patients with severe forms of PID still face significant challenges of short and long-term transplant-related complications. Novel HSCT strategies are being implemented aiming to improve both survival and long-term quality of life. This article will discuss the latest developments in HSCT for PID, and present data regarding approach and outcome of HSCT in recently described PIDs, including disorders associated with immune dysregulation.